HUMAN RESOURCES DEVELOPMENT FOR THE EFFICIENT OPERATION OF THE ORGANIZATION - GAJDA, Joanna (Trends in education, 2013)
Performance arrangement requires to adjust human potential to the environment in which the organization operates is a necessity today. The company management has a task to prepare well skilled employees, and the company managers are responsibile for the staff planning, which should include job analysis such as forecast of labor demands and supply. In this article we examined the factors determining the effectiveness of the process.
Keywords: plan; source of information for human resource planning; planning methods